EFFECT OF CHROMIUM ON GROWTH AND YIELD OF Vigna mungo (L.) - A. K. MURUGAN, P. SUNDARAMOORTHY,; GANESH, K. SANKAR (Journal of Plant Stress Physiology)
This study was conducted to find out the effect of different concentrations (control 5, 10, 25, 50, 100 and 200 mg/l) of chromium on growth, yield of black gram (Vigna mungo L.). Pot culture experiments were carried out with black gram seeds with different concentrations of chromium solution. The morphological growth parameters were recorded at 15, 30, 45 and 60 days old chromium treated plants. The yield was recorded at the time of harvest. The study revealed that, the increase in chromium reduce the growth and and yield in black gram plants.